KKN PPM Dissemination and Outreach to the Community Anti-Drug - Iip Istirahayu; Mardian Mardian; Nurhayati Nurhayati; Gu Fangyu (STKIP Singkawang, 2018)
KKN PPM program objective is to provide insight to junior high school students about drugs and its effects. The program is carried out in SMPN 8 Singkawang through socialization and counseling. There are three things to be done to optimize this service activity. Sosialiszation iwill be given in order to provide information about various drugs and counseling to avoid drugs in order to avoid the impact of which is not good.